The Strategy of Islamic Education to Prevent Radicalism: A Case in Diponegoro University, Indonesia - Wibowo, Arif (Tadibia Islamika: Journal of Holistic Islamic Education, 2021)
The aim of this research is to investigate the strategies employed by Diponegoro University in Islamic Religious Education to counteract radicalism. Additionally, it seeks to analyze the factors that either support or hinder these strategies. Employing a qualitative approach with a descriptive method, this research involves data collection through interviews, observation, and documentation. Data analysis follows a descriptive process encompassing data reduction, data presentation, and the formulation of conclusions. Diponegoro University has adopted a multi-faceted strategy to combat radicalism, which includes the formation of a specialized anti-radicalism team known as TIMARU. This initiative is undertaken collaboratively with various stakeholders. Moreover, the university has devised a comprehensive curriculum aimed at countering radical ideologies. This curriculum is further fortified by organizing public lectures, seminars, and Forum Group Discussions addressing topics related to national identity and anti-radicalism. To engage students, the university also provides avenues for the expression of talents and interests through extracurricular activities. Several factors contribute significantly to the success of these strategies at Diponegoro University. These include access to adequate facilities and infrastructure, a proficient team of human resources, strong collaboration among all segments of the academic community, and the implementation of a comprehensive strategy. Furthermore, the existence of a specialized team dedicated to countering radicalism has proven instrumental in these efforts. However, certain obstacles persist, including the absence of a technical team in the field, lengthy and intricate regulations, and an unstructured hidden curriculum.In summary, this research delves into the strategies employed by Diponegoro University's Islamic Religious Education to combat radicalism. It underscores the multifaceted nature of these strategies, including the establishment of TIMARU, comprehensive curricular initiatives, and extracurricular activities. While the university benefits from various supporting factors, challenges such as the absence of a technical team and complex regulations remain to be addressed.